2021
DOI: 10.1038/s41598-020-79576-5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of streamflow alteration on benthic macroinvertebrates by mini-hydro diversion in Sri Lanka

Abstract: Our study focused on quantifying the alterations of streamflow at a weir site due to the construction of a mini-hydropower plant in the Gurugoda Oya (Sri Lanka), and evaluating the spatial responses of benthic macroinvertebrates to altered flow regime. The HEC–HMS 3.5 model was applied to the Gurugoda Oya sub-catchment to generate streamflows for the time period 1991–2013. Pre-weir flows were compared to post-weir flows with 32 Indicators of Hydrologic Alteration using the range of variability approach (RVA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…A decline in invertebrate density with flow reduction has been reported elsewhere (Martínez et al, 2020;Matthaei et al, 2010), but our study adds that this negative effect is more common in the polluted rivers, showing signs of an intensification of diversion effects with pollution. Similarly, other studies have shown that water diversion reduces local diversity (Munasinghe et al, 2021), due to the reduced habitat diversity (Cazaubon & Giudicelli, 1999). In our study, we demonstrate that α diversity is negatively affected by diversion only interactively with pollution, as the reduction was only obvious in the most polluted river.…”
Section: Pollution Accentuated the Response Of Food Webs To Water Div...supporting
confidence: 83%
See 1 more Smart Citation
“…A decline in invertebrate density with flow reduction has been reported elsewhere (Martínez et al, 2020;Matthaei et al, 2010), but our study adds that this negative effect is more common in the polluted rivers, showing signs of an intensification of diversion effects with pollution. Similarly, other studies have shown that water diversion reduces local diversity (Munasinghe et al, 2021), due to the reduced habitat diversity (Cazaubon & Giudicelli, 1999). In our study, we demonstrate that α diversity is negatively affected by diversion only interactively with pollution, as the reduction was only obvious in the most polluted river.…”
Section: Pollution Accentuated the Response Of Food Webs To Water Div...supporting
confidence: 83%
“…These structures have multiple effects on ecosystems. The barriers themselves disturb the dispersion of aquatic organisms across the fluvial network (Jones et al., 2020), which affects community structure (Munasinghe et al., 2021). Additionally, water diversion driven by these infrastructures can modify environmental conditions through narrowing wetted channel, reducing flow velocity and water depth and altering water physico‐chemistry (Dewson et al., 2007a), which leads to changes in community abundance and diversity (Munasinghe et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These low abundance and richness of the community would be the consequence of the increase in speed and water depth. Reference [50] go further by saying that the increase in water flow leads to a reduction in taxonomic richness. Both spatially and temporally, no community has reached maximum diversity due to the constant renewal of taxa.…”
Section: Biological Characteristics Of Sampling Stationsmentioning
confidence: 99%
“…The method was repeated thrice in different places within a 10-m reach in the river to sample diverse velocity regimes and habitats until the 1 m 2 region had been covered. Hand-collected samples were also taken from individual boulders in the water 61 . The samples were kept in 100% ethanol for long-term storage until the identification process was finished.…”
Section: Methodsmentioning
confidence: 99%